2002
DOI: 10.1667/0033-7587(2002)157[0099:entbmx]2.0.co;2
|View full text |Cite|
|
Sign up to set email alerts
|

Enhanced Neoplastic Transformation by Mammography X Rays Relative to 200 kVp X Rays: Indication for a Strong Dependence on Photon Energy of the RBEMfor Various End Points

Abstract: The fundamental assumption implicit in the use of the atomic bomb survivor data to derive risk estimates is that the gamma rays of Hiroshima and Nagasaki are considered to have biological efficiencies equal to those of other low-LET radiations up to 10 keV/microm, including mammography X rays. Microdosimetric and radiobiological data contradict this assumption. It is therefore of scientific and public interest to evaluate the efficiency of mammography X rays (25-30 kVp) to induce cancer. In this study, the eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
50
2
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(57 citation statements)
references
References 34 publications
4
50
2
1
Order By: Relevance
“…Having seen oncotransformation potential than the 200 kVp X-rays, suggesting that the low-energy X-rays used in mammography are considerably more biologically active than previously thought. [9][10][11] This finding is consistent with data on chromosome aberration induction by low-energy X-rays. 12 Furthermore, it is now well-accepted that even low doses of IR can cause oxidatively generated clustered DNA lesions.…”
Section: Ir-induced Microrna Expression In Mammary Gland Cellssupporting
confidence: 90%
“…Having seen oncotransformation potential than the 200 kVp X-rays, suggesting that the low-energy X-rays used in mammography are considerably more biologically active than previously thought. [9][10][11] This finding is consistent with data on chromosome aberration induction by low-energy X-rays. 12 Furthermore, it is now well-accepted that even low doses of IR can cause oxidatively generated clustered DNA lesions.…”
Section: Ir-induced Microrna Expression In Mammary Gland Cellssupporting
confidence: 90%
“…Another means by which prone treatment could become a viable standard treatment option is to optimize verification. CBCT as used here and in NYUH is one possibility but, given the potential long-term risks of exposure to low-dose ionizing radiation (20,21), may not be justifiable in the context of patients with low-risk disease, especially given that the basis for pursuing prone treatment is reduction of long-term side-effects. Other technologies that can be used to localize soft tissue targets include implanted transponder systems, implantable dosimeters, and opto-electronic surface imaging (22)(23)(24).…”
Section: Discussionmentioning
confidence: 99%
“…During recent years there have been several reports about an enhanced risk from exposure to soft x-rays (up to -50 kV) compared to conventional x-rays or ?-rays [ 1,2]. It has been shown that soft x-rays can be more effective in cell killing [3,4,5,6], induction of chromosome aberrations [7,8,9] and neoplastic transformations [6]. Virsik et al [7] found higher yields of dicentric chromosomes in human lymphocytes for 30 kV x-rays compared to 150 kV x-rays resulting in RBE values of 1.25 up to 3 for high and low doses, respectively.…”
Section: Introductionmentioning
confidence: 99%